Late time window endovascular treatment for acute ischemic stroke: rethinking the role of simplified imaging - Zongjie Shi; Sujie Zheng; Xinzhao Jiang; Xu Wang; Yu Geng (BMC Neurology)
Abstract Objective To assess safety and efficacy of endovascular treatment (EVT) in acute ischemic stroke (AIS)patients selected by ASPECTS within 6–24 h after onset. Methods Patients were divided into early and late time window groups. Primary outcome was 90-day mRS 0–2, safety outcomes were 90-day any intracranial hemorrhage (ICH) and mortality. Univariate and multivariate analyses were conducted for the prediction of good outcome. Results Of the 296 patients screened, 242 patients fulfilled the study criteria. Patients in the late time window group were younger, had lower baseline NIHSS scores and ASPECTS, a lower proportion of atrial fibrillation, a higher proportion of large-artery atherosclerosis, less received intravenous thrombolysis, and had a longer time from symptom onset to treatment. No difference in primary and safety outcomes: good outcome (42% vs. 50.5%, p = 0.188), ICH (26.1% vs. 20.6%, p = 0.311), and mortality (18% vs. 9.9%, p = 0.067). Multivariate analysis showed that age (OR = 0.977, 95%CI 0.955–0.999, p = 0.039), NIHSS score (OR = 0.905, 95%CI 0.858–0.953, p = 0.001), ASPECTS (OR = 1.242, 95%CI 1.004–1.538, p = 0.046), glucose (OR = 0.817, 95%CI 0.720–0.926, p = 0.002), platelet (OR = 1.005, 95% CI 1.000 -1.010, p = 0.031) and successful recanalization (OR = 5.037, 95%CI 1.137–22.318, p = 0.033) were independent predictors of good outcomes. Conclusions For late-window acute anterior-circulation LVO patients, those selected based on the ASPECTS exhibited comparable 90-day good outcomes and safety profiles to those in the early time window. This finding implies that ASPECTS could serve as a screening tool for patients in the late time window when undergoing EVT. Clinical trial This is a clinical retrospective study. However, at the time when the study was initiated, clinical trial registration was not a mandatory requirement. Therefore, this trial was not registered.